Weight Structure Of Roman Denarii, 138-161 - Jarzęcki, Krzysztof (Acta Archaeologica Lodziensia, 2019)
The purpose of the paper is the presentation and interpretation the weight parameters of denarii minted in Rome in the years 138-161. The data, on which these considerations are based, are from published information about coins from trade, collected and ordered by the author. Table 1 shows the weight of Antoninus Pius’ denarii. Table 2 shows the numbers of denarii of Antoninus Pius in individual weight ranges. Tables 3 and 4 shows similarly the weight and numebers of denarii of the empress Faustina I in individual weight ranges. Table 5 shows the number of denarii of Marcus Aurelius, struck during the lifetime of Antoninus Pius, in individual weight ranges. Table 6 shows similar data about denarii of Faustina II. Comparative analysis of the data presented in Tables 1-6 allows to indicate a series of denarii with similar quantitative weight parameters. According to the author, it is very likely that they were “twin” series, which means that they were contemporary. The series of denarii selected in this way are shown in Table 7. This allows to narrow down the chronology of some denarii of Antoninus Pius and Marcus Aurelius, for example denarii RIC 127 for the years 145-(147?), instead of the traditional 145-161 and propose precise chronology of some series of denarii of Faustina I and II. Acceptance of the “twin” series hypothesis is particularly important in the context of consideration of the detailed chronology of Roman empresses coins.